Transformation toward Indonesia Emas 2045: Some Issues and Challenges - Bakti Setiawan (Pusbindiklatren Bappenas, 2026)
It is quite difficult to actually prepare Editorial Notes which deliver 15 papers selected in this edition. Not only are the fifteen papers very interesting and important, but the variety is also quite wide, ranging from discussions on smart governance, disaster and social capital, waste issues, regional planning, transport management, to public private partnerships (PPP). Through a long reflection, I come to conclude that all of the papers seem to reflect how diverse issues and challenges we face, both on a local, national, and global scale. These issues and challenges are very relevant for us to continue to discuss and find solutions, especially in the framework that this great nation is just in the process of extraordinary transformation, to ensure the achievement of the Indonesia Emas (Golden Indonesia), as stated very clearly and sharply in our Long-Term Development Plan document (RPJMN 2025 – 2045). The following descriptions attempt to underline some of the important issues and challenges we face, as reflected in the fifteen papers in this edition.